Effects of pulping conditions and processing variables on the performance of kenaf medium density fibre board - Nayeri, Majid Dehghan (2014)
Kenaf, Hibiscus cannabinus L., is a environmentally friendly crop which is recognized as one of the potential lignocellulosic material to replace wood in different kinds of wood based products. Kenaf has excellent properties for pulp and paper, medium density fibre board (MDF), and other composites, as it has a low density, little abrasion during processing, high filling levels, and high specific mechanical properties. The kenaf stem is composed of an outer layer (bast) and a core which either by chemicals and/or by enzymatic retting it is easy to separate. The bast constitutes 25 to 40% of the stem dry weight and shows a dense structure. Alternatively, the core is wood-like and makes up the remaining 60 to 75% of the stem. Both portions are greatly different ties in terms of anatomy, physical and chemical content. Studies concerning the production of medium density fibre board (MDF) with kenaf as an alternative fibrous material have been carried out as an attempt to provide a sustainable and viable destination for this lignocellulosic material. This work aimed to evaluate the properties of kenaf fibres at different refining conditions and to produce kenaf MDF of acceptable strength. In this dissertation, MDF was prepared from kenaf and rubber wood and their mixture. The parameters of preparation and the resulting intermediate products as well as the final products, MDF, were characterized and compared at each experimental step. The investigation of fibre dimensions based on pulping of bast and core fibre resulted in different behavior of the two classes of fibre. There are significant variations in all aspects of fibre morphology of bast fibre at different pulping temperatures and pulping time, and a significant interaction was detected between both parameters. The bast fibre produced longer and thinner fibre, compared to the core fibre, thus yielding fibre of higher aspect ratio. The changes in fibre morphology were clear when the pulped temperature increased. The core fibre exhibited significant variations in fibre length, fibre width, and wall thickness in all parameters. The lumen diameter and aspect ratio fibre width, and wall thickness in all parameters. The lumen diameter and aspect ratio were not significantly affected by differences in pulping temperature, pulping time, and the interaction between both parameters. The fibre width was reduced at an increasing pulping temperature and time, but lumen diameter was not significantly affected. The aspect ratio also decreased with increasing pulping temperature and time. The length of core fibre decreased with increasing pulping temperature and pulping time. The fibre width shows constant reduction as the pulping condition become more severe. Consequently the Runkel ratio was decreased also. The pH value of both fibres was reduced as the temperature increased; core fibre was more acidic (pH= 3.8) compared to bast fibre (pH= 4.5). It is evident from results that bast fibre is more resistant to acid and displayed greater acid buffering capacity compared to core fibre. The investigation of the effect of refining pressure (6 and 8) and resin content (10, 12, 14 %) on physical (WA and TS), and mechanical (MOE, MOR, IB) properties MDF made from a mixture of biomass kenaf (Hibiscus cannabinus L.) stem and rubberwood showed thermo-mechanical refining and resin content were influential in the increment of physical and mechanical properties of the MDF. For 8 bar of refining pressure with 14% resin content, the MDF recorded optimum WA of 83.12%, TS of 20.2%, MOR of 25.3 MPa, MOE of 3450 MPa and IB of 0.51 MPa [density 700 (kg/m3)]. Response surface methodology was used to establish the optimum process variables (resin content, and pressure) for effect on board properties. By using response surface and contour plots, the optimum set of operating variables can be obtained graphically, in order to achieve the desired board properties. Therefore, it was recommended that the board properties increase when the resin content and pressure increased. It can be inferred that any parameters, individually, had a positive effect on the increase of board properties. The main effects of parameters are in following order: main effect of resin content> pressure.